To use or not to use: Safety of selected painkillers in patients with chronic liver diseases - Rorat, Marta J.; Szymański, Wojciech; Zińczuk, Aleksander (Clinical and Experimental Hepatology, 2025)
Safe and effective pain treatment for patients with chronic liver diseases (CLD) often poses a challenge in clinical practice. The widespread use of painkillers can lead to drug-induced liver injury. CLD can alter drug response by affecting drug-metabolizing enzymes and half-life, thereby impacting the strength and safety of drug use. This study reviews the safety and hepatotoxicity of selected analgesics in CLD. Paracetamol is the safest drug when used in standard doses. Metamizole is not contraindicated for short-term treatment. Non-steroidal anti-inflammatory drugs should be avoided due to their significant hepatotoxic potential. Tramadol is not recommended for cirrhosis due to its unpredictable effects. Codeine should also be avoided. Proper management includes the selection of drugs based on factors such as the type and severity of pain, duration of treatment, patient sensitivity, drug interactions, stage of liver disease, and the presence of other conditions. Patients should be closely monitored for adverse effects.